Cancer connect - Tan, Yong Lin (2013)
Cancer is a prevalent problem in Singapore today, but there is a general lack of self-help articles on how cancer patients can ease their day-to-day life. Relevant information to aid caregivers of these cancer patients is also lacking and at times non-existent. For these caregivers in Singapore, they need an avenue to seek or receive support as compared to cancer patients. While cancer patients would be given proper psychological counselling (if required), interaction sessions with fellow cancer survivors as well as multiple avenues for them to share any issues they might be having, caregivers on the other hand do not have the same opportunity and channels to seek support like cancer patients do.